2001
DOI: 10.1046/j.1365-2311.2001.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of sperm precedence in a noctuid mothHeliothis virescens: a role for male age

Abstract: Summary 1. Females of the noctuid moth Heliothis virescens F. mate more than once. Thus, sperm from two or more males normally compete for fertilisations within the female reproductive tract. The eggs are typically fertilised by sperm from only one male, either the female's last mate or an earlier mate. Twice‐mated females store only one ejaculate's worth of fertilising sperm (eupyrene) but nearly two ejaculates' worth of a nonfertilising sperm morph (apyrene), which is thought to play a role in sperm competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
1
24
1
1
Order By: Relevance
“…These results are in contrast to previous studies in this system that showed the second (last) male generally obtained precedence over the first (Flint and Kressin 1968, Pair et al 1977, LaMunyon 2001. This study shows the importance of long-term observations to assess paternity allocation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results are in contrast to previous studies in this system that showed the second (last) male generally obtained precedence over the first (Flint and Kressin 1968, Pair et al 1977, LaMunyon 2001. This study shows the importance of long-term observations to assess paternity allocation.…”
Section: Discussioncontrasting
confidence: 99%
“…The first two scenarios have been called 'sperm precedence' (Svärd andMcNeil 1994, Simmons 2001). The third scenario leads to multiple paternity (LaMunyon 2001, Simmons 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm competition and sperm precedence have been measured in Hv as well (72)(73)(74)(75)(76). Sperm precedence typically occurs, although the eggs are not always fertilized by sperm from the last male to mate but by sperm from the oldest male (74).…”
Section: Discussionmentioning
confidence: 99%
“…The females have 2 genital openings, and it is believed that additional spermatophores cannot be connected to the genital openings because they are full. We modified existing DAPI protocols used for insects, bacteria and blue-green algae to stain the spermatozoa before counting (Porter & Feig 1980, LaMunyon 2001. The females were killed by freezing at −18°C.…”
Section: Expt 4: Size Of the Spermatophorementioning
confidence: 99%